Production sharing contracts in Indian oil & gas sector - Pandey, Ajay, (SAGE knowledge. Cases., 2016)
The case describes the policies followed by the Indian government to attract private investments for oil & gas exploration. This case is based around observations made by the Comptroller and Auditor General of India on some of the petroleum sharing contracts and the remedial measures suggested by a committee appointed by the government.